Effect of glittered nail polish on pulse oximetry measurements in healthy subjects - Mohammadreza Yeganehkhah; Tahmineh Dadkhahtehrani; AhmadReza Bagheri; Ahmad Kachoie (Wolters Kluwer Medknow Publications, 2019)
Background: Pulse oximeter is a simple and noninvasive standard device to monitor the saturation of peripheral oxygen (SpO2) and heart rate. The nail polish of different colors may result in inaccurate oximetry reading and interpretation of oxygen saturation. This study aimed at determining the effect of different colors of glittered nail polish on SpO2in healthy students. Materials and Methods: This is a randomized clinical trial on 30 healthy students with SpO2≥95% and without any complications on nail beds and environmental perfusion. SpO2was measured on 10 fingers of the participants after sitting and resting on a seat for 10 min in a room with normal temperature. Then they were asked to apply 10 colors of glittered nail polish randomly to their fingernails as all colors were used. After drying the two-layer nail polish, SpO2was measured again. Results: Of 10 glittered nail-polishes, dark green and purple did not change SpO2reading significantly. All other colors lowered SpO2significantly based on Wilcoxon test (red: p = 0.003; orange: p = 0.002; yellow: p = 0.015; pink: p = 0.017; dark blue: p = 0.001; violet: p = 0.001; brown: p = 0.001; black: p = 0.001). However, those changes were not clinically significant because SpO2differences before and after nail polish were in acceptable range (less than a 2% change). Conclusions: We conclude that different colors of glittered nail polishes do not result in a clinically significant change in pulse oximetry measurements in healthy subjects; therefore, it is not necessary to remove the glittered nail polish routinely in clinical, surgical, and emergency settings.